Career aspirations of dental students: insights from a multinational study using social cognitive career theory (SCCT) - Riad, Abanoub; Elsheikh, Lamis; Domnori, Silvi; Doris Fratila, Aurora; Carter, Charlotte; Kaya, Deniz Devrim; Volevach, Ekaterina; England, Rachael; Morgado, Mariana; Issa, Julien; Attia, Sameh; Armstrong, Mick; et al. (Frontiers in Oral Health, 2025)
BackgroundDental students' career choices are shaped by many factors, including their personal abilities and goals, environmental factors and the resources available to them. Understanding the drivers for this career pathway decision is crucial for educational institutions' development of comprehensive curricula. This study applies Social Cognitive Career Theory (SCCT) to investigate the professional aspirations of dental students globally, providing insights into the factors that influence career choices of dental students from different regions to understand how personal, socioeconomic and cultural differences influence their decisions.MethodsA cross-sectional, multicentred survey was conducted between May and July 2023, involving 1964 dental students from over 20 countries. Self-administered questionnaires based on SCCT were used to assess participants' self-efficacy, professional and personal outcome expectations, career goals, and career path preferences. Statistical analysis, including multivariable logistic regression and mediation analysis, was employed to identify the relationships between the SCCT framework, sociodemographic factors and career aspirations.ResultsThe study revealed that 51.2% of participants preferred a specialty in clinical dentistry, while 28.1% aimed for general dentistry. Mediation analysis demonstrated notable pathways from career planning training to career aspirations through self-efficacy, professional and personal expectations. Self-efficacy mediated 26.7%–98.65% of the effect on career preferences coming forward as a key mediator. Demographic statistics demonstrated that regional and economic differences significantly impacted students’ career choice, where students from higher-income countries reported more likely to choose general dentistry and those from lower-income countries were more drawn to specialty fields or public health.ConclusionsThis study offers new insights into the global career aspirations of dental students through the prism of the SCCT. These findings highlight the need for dental schools and associations to offer tailored career planning training based on students' backgrounds at an early phase of their education. Providing support and career guidance, especially in underserved regions, can help students make informed decisions that align with their personal and professional goals. This will ultimately contribute to a more diverse and well-prepared global dental workforce.